IMPLEMENTATION OF KHIYAR RU'YAH IN HOME INTERIOR ORDER TRANSACTIONS IN THE PERSPECTIVE OF FIQH MUAMALAH - Muhammad Yusran Hadi; Fazrul Azis (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2024)
The pre-order transaction for the interior of the house is generally agreed upon at the beginning of the contract, while the payment is made by making a panjar and repayment after the product is installed in the consumer's home. Of course, consumers always want the interior products made to be of high quality and special in accordance with the desired shape and size, but sometimes the results of the ordered goods do not match expectations and contracts. This research was conducted to answer the question, how is the application of khiyar ru'yah in ordering interior products and how is the perspective of bai' istishna' on the application of khiyar ru'yah. This research uses descriptive analysis method with primary data sources obtained from field research and secondary data from literature research. The results of this study indicate that the agreement made by the owner and his customers in Kuta Raja is partly in writing and partly orally, and the application of khiyar ru'yah rights in interior order transactions, the seller gives the buyer the opportunity before making a payment to first check the interior product that has been completed, if an error is found the interior gives responsibility in the form of repairing the product or providing compensation whose amount is not agreed upon at the beginning, if the product cannot or is difficult to repair. It is concluded that the practice of khiyar ru'yah has been applied, but based on the perspective of bai' istishna' the application of khiyar ru'yah is not perfect, because the customer may not cancel the order if the ordered goods do not match the agreed form.